A method for improving the reaction degree of fly ash-based geopolymer
By performing multi-step polymerization reaction and detection in fly ash geological polymers, combined with heating and curing, the problem of unreacted fly ash particles is solved, and the reaction degree and mechanical properties of fly ash geological polymers are significantly improved.
Patent Information
- Application Number
- CN202410101305.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-23
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-01-23
AI Technical Summary
In the prior art, there are a large number of unreacted fly ash particles during the maintenance process of fly ash geological polymers, resulting in unevenness of the earth polymer, affecting its mechanical and durability performance, and it is difficult for existing methods to effectively improve fly ash. The degree of reaction of the particles.
By determining the amount of fly ash, NaOH and Na2SiO3, a polymerization reaction was performed to obtain dipolymer A and a secondary polymerization reaction was performed in alkali liquid. The time of the secondary polymerization reaction was detected by ICP-MS, and then the maintenance was carried out at room temperature. and optional heating and maintenance to improve the reaction level.
The reaction degree and mechanical properties of fly ash geological polymers are improved, the increase period of compressive strength is extended, and the final performance of fly ash geological polymers is significantly improved.
Smart Images

Figure CN117945708B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fly ash-based geopolymer maintenance, in particular to a method for improving the reaction degree of fly ash-based geopolymer. Background Art
[0002] Geopolymer is a kind of low-carbon building material with high attention. It is considered as an alternative material to ordinary Portland cement (OPC) due to its excellent mechanical and durability properties and various advantages. In particular, it has low carbon emissions. Among them, fly ash-based geopolymer composites produce about 40% to 60% less CO2 than OPC systems during their manufacturing process. Geopolymer belongs to the category of alkali activated materials (AAM). Its gelling phase basically uses pure aluminosilicate or similar raw materials. It is a gel system obtained by the reaction of alkali metal raw materials (solid or solution) and solid silicate powder. In order to form a gel with the main gelling phase, the calcium ion content allowed by the reaction components is usually very low to form a zeolite network structure instead of a chain of hydrated calcium silicate. Among them, low-calcium fly ash is the most common raw material in the artificial synthesis of geopolymers. For fly ash-based geopolymers, due to the low calcium oxide content of low-calcium fly ash, the polymerization degree of [SiO4] tetrahedron is very high and it is almost insoluble in water. Therefore, the dissolution-depolymerization process of fly ash must be carried out under certain alkaline conditions, that is, the synthesis reaction of fly ash-based geopolymer is a solid-liquid two-phase reaction between solid fly ash particles and alkaline activator solution. Generally speaking, the alkaline activator solution is made by mixing sodium silicate solution and sodium hydroxide solution in a certain proportion, and the activating effect is more prominent.
[0003] There are many factors that affect the reaction of geopolymers, including raw material composition, activator type, water content, Si / Al ratio, curing method, etc. Among them, the curing method controls the formation of alkali-active materials to a large extent. For example, the increased temperature increases the rate of chemical reactions and the dissolution of active substances, thereby increasing the interaction between the aluminosilicate source and the alkaline solution during geopolymer synthesis.
[0004] At present, there are many curing methods, including normal temperature curing in air, normal temperature curing in sealed bags, normal temperature curing in water, high temperature steam curing, high temperature water curing, hot air box curing, etc. There are also composite curing methods, such as curing under high temperature conditions for 1 day, demolding, and then continuing curing under standard conditions at room temperature (G+C); or first pre-curing the sample under standard conditions at room temperature for 1 day, demolding, and then continuing curing under high temperature conditions (C+G). Among them, high temperature environment has been confirmed by most scholars to be the most favorable factor for accelerating polymer reaction. In addition, the polycondensation reaction of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron is a dehydration reaction, and excessive moisture during curing is not conducive to geopolymerization reaction. Therefore, hot air box curing is currently the most commonly used curing method for preparing high-strength fly ash geopolymer. However, in the process of analyzing the above-mentioned various curing methods, it was found that at the microscopic level of the geopolymer, there is a large amount of fly ash that does not participate in the reaction, which plays a filling role in the paste. There are gaps in the transition area between the unreacted fly ash and the paste interface, which is likely to affect the final properties of the geopolymer, including mechanical and durability properties.
[0005] During the crystallization and hardening stage of fly ash geopolymer, the gel precipitates on the surface of fly ash particles, which hinders the corrosion and dissolution of fly ash particles by alkaline solution. At this time, the reaction rate slows down and the excitation effect is mainly controlled by diffusion, that is, it depends on OH - The ability to penetrate the surface of fly ash particles through the gel layer. As the gel on the surface of fly ash particles increases, the unreacted fly ash particles are finally bonded together to form fly ash-based geopolymer. The slurry completely hardens into a solid and has a certain strength. Therefore, the formed geopolymer is a heterogeneous body, including aluminum silica gel and unreacted fly ash particles.
[0006] At present, the only way to improve the reactivity of fly ash particles is to - control to improve, but higher OH - It will also affect the final formation of the paste. Therefore, in order to better adjust the reaction degree of fly ash particles and ensure the final performance of geopolymer, it is necessary to set up a new composite curing method. Summary of the invention
[0007] In order to overcome the above-mentioned defects existing in the prior art, the present invention provides a method for improving the reaction degree of fly ash-based geopolymer. Through this method, while ensuring the molding of geopolymer, the reaction degree of fly ash particles is improved, the final mechanical properties of fly ash geopolymer are improved, and the use value of geopolymer is increased.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0009] The present invention provides a method for improving the reaction degree of fly ash-based geopolymer, comprising the following steps:
[0010] (1) Determine the amount of fly ash, obtain the unknown amounts of NaOH, Na2SiO3 and water through formulation design, and perform a polymerization reaction of fly ash, NaOH, Na2SiO3 and water to obtain geopolymer A;
[0011] (2) Soaking geopolymer A in alkali solution to carry out a secondary polymerization reaction to obtain geopolymer B;
[0012] (3) Determine the time of secondary polymerization reaction by inductively coupled plasma mass spectrometry (ICP-MS);
[0013] (4) After heating and curing the geopolymer B, it can be kept at room temperature until the curing age.
[0014] Optionally, the coordination design method in step (1) includes:
[0015] S1. Determine the liquid-solid ratio, exciter modulus, OH - molar concentration, the liquid-to-solid ratio is the ratio of the sum of water and solid, the activator modulus is the SiO2 / Na2O ratio after the composite activator is prepared by NaOH and Na2SiO3, the OH - Molar concentration refers to NaOH solutions of different molar concentrations;
[0016] S2. Determine the amount of fly ash, and count the unknown amounts of Na2SiO3, NaOH and water as A, B and C. The specific calculation method is:
[0017]
[0018]
[0019]
[0020]
[0021]
[0022] in, is the concentration of sodium silicate solution; FA is the mass of fly ash; is the modulus of sodium silicate solution; Sodium silicate solution Content; Sodium silicate solution Content; Sodium hydroxide powder The content.
[0023] Optionally, the concentration of the alkali solution in step (2) is designed to be:
[0024] The geopolymer A prepared in step (1) is immersed in NaOH of different molar concentrations at room temperature; the concentration can be designed according to the concentration of the alkali solution in the preparation ratio;
[0025] Geopolymer A is immersed in a volume of 1000cm 3 The concentration test is carried out in a solution with a solid-liquid ratio of 0.0626-0.25; after immersion, the immersion solution concentration of the sample that has not cracked and is relatively complete is selected as the alkali solution concentration.
[0026] Optionally, the concentration of NaOH may be three samples of two identical concentrations and one different concentration;
[0027] The soaking time is 7 to 10 days;
[0028] When the polymer does not crack at two different concentrations, the higher concentration is selected as the alkali solution concentration.
[0029] Optionally, the inductively coupled plasma mass spectrometry method in step (3) includes:
[0030] During the soaking process of step (2), sampling is performed at different time intervals, and the solution is collected after filtering and dilution;
[0031] The obtained solution was detected by inductively coupled plasma mass spectrometry (ICP-MS), and the dissolution curves of Si and Al elements were drawn. The time period of secondary precipitation was determined by finding the descending section of the dissolution of Si and Al elements in the fly ash polymer, thereby determining the end time of the secondary polymerization reaction.
[0032] Optionally, at least one of the following conditions is met:
[0033] The time interval is 4 to 16 hours;
[0034] The amount of the sampling solution is 1-3 ml;
[0035] The filtering method is a conventional syringe filter filtration in the art. When a syringe filter is used for filtration, the diameter of the syringe is 0.1-0.5 μm.
[0036] The dilution multiple is 20 to 100 times.
[0037] Optionally, the heating and curing method in step (4) is to place the mixture in a hot air oven for heating and curing;
[0038] When the hot air box is used, the temperature of the heating and curing is 60-80°C;
[0039] When the hot air box is used, the heating and curing time is 24 to 48 hours.
[0040] Optionally, the nursing period in step (4) is 5 to 10 days.
[0041] Fly ash is a byproduct of thermal power generation. It is collected by bag filters or electrostatic precipitators to remove particles from flue gas, making the flue gas cleaner and less harmful to the environment. Fly ash is composed of fine spherical glass particles of different sizes, and its chemical composition is mainly SiO2, Al2O3, Fe2O3 and CaO. The chemical composition of fly ash depends on the type of coal burned, the type of material and airflow injected into the furnace to reduce flue gas pollutants, and the particle collection efficiency of the dust collector. When limestone or dolomite is used as a desulfurization material for tail gas, the CaO and MgO content in fly ash will increase. Sulfur trioxide, sodium carbonate, bicarbonate, sodium sulfate, phosphorus, magnesium oxide, water, ammonia and triethylamine are often used as regulators to improve dust collection efficiency. Fly ash also contains some irregular or angular incompletely burned carbon particles and mineral particles.
[0042] According to ASTMC 618 (2003) standard, fly ash with (SiO2+ Al2O3+ Fe2O3)>70% is classified as Class F fly ash, and fly ash with 70%>(SiO2+ Al2O3+ Fe2O3)>50% is classified as Class C fly ash. Both fly ashes are spherical particles with no obvious difference in size and shape, but Class F fly ash has a smooth surface, while alkali and sulfide are sometimes deposited on the surface of Class C fly ash particles.
[0043] The most abundant phase in fly ash is glass. The crystalline compounds in fly ash include quartz, mullite, hematite, spinel, magnetite, calcite, calcite, calcium sulfate and alkali sulfate, accounting for about 5% to 50% in total. High calcium ash contains a certain amount of free CaO, C3A, C2S, CaSO4, MgO and 4CaO • Al2O3• SO3. X-ray diffraction technology can accurately identify the crystalline phase substances in fly ash. The diffuse peak in the fly ash X-ray spectrum is caused by the glass phase, and its position depends on the lime content in the fly ash.
[0044] Class F fly ash has a low CaO content, so it has little or no hydraulic properties. Class C fly ash, in addition to the glass phase, also has a certain amount of crystals such as CaO, C3A, C2S, CaSO4, MgO and 4CaO •3Al2O3• SO3, so Class C fly ash itself has a certain hydraulic property. The hydration behavior of C3A and C2S in fly ash is the same as that in Portland cement. Many researchers believe that the hydraulic properties of Class C fly ash are due to the crystalline phase it contains. The glass phase with a high lime content has a high hydraulic activity and exhibits self-hardening cementitious properties.
[0045] Compared with the prior art, the beneficial effects of this application include:
[0046] (1) The type of coal burned basically determines the type of fly ash. This application is aimed at fly ash with complex composition. Under the conditions of determined curing conditions such as temperature and time, the method provided in this application can improve the mechanical properties of fly ash geopolymer while effectively improving the degree of fly ash reaction.
[0047] (2) Although traditional methods can improve the mechanical properties of polymers, the present application has found through research that although the compressive strength continues to increase with the extension of curing time, in most cases, the increase in compressive strength mainly occurs in the first 28 days of curing, and the curing thereafter has little to do with the increase in compressive strength. Therefore, the present application improves the reaction degree of ions inside fly ash under certain conditions, thereby fundamentally improving the mechanical properties of fly ash geopolymers. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0049] Figure 1 is the dissolution curve of Si and Al elements in 4M-EC-8 in Example 1;
[0050] Figure 2 The SEM comparison of the alkali immersion-heating curing specimen (b) and the traditional high temperature curing specimen (a) in Example 1;
[0051] Figure 3 This is a force-displacement curve diagram after 7 days of casting in Example 1, where blue is 8M (specimen cured at room temperature), red is 8M-70 (traditional high-temperature cured specimen), and green is 4M-EC-8-70 (curing method provided in this application). DETAILED DESCRIPTION
[0052] Example 1
[0053] Raw material ingredients:
[0054] The fly ash content is shown in Table 1, (SiO2+Al2O3+Fe2O3)=91.21%>70% is Class F fly ash, where the Si / Al molar ratio is 1.16, suitable for preparing cementitious materials, and the calcium oxide content is 3.53%, which is low-calcium fly ash; liquid sodium silicate, where the modulus is 2.31 and the content is 42%; white flaky sodium hydroxide.
[0055] Table 1 Fly ash composition content
[0056]
[0057] NaOH solutions with molar concentrations of 6 M, 8 M, and 10 M were prepared. For the alkaline activator solution, the SiO2 / Na2O ratio used was 1.04. The liquid-to-solid ratio was tested for the best working performance and was designed to be 0.27, as shown in Table 2 below.
[0058] Table 2 Alkaline activator solution preparation table
[0059]
[0060] Select 4M-EC-8 by observation and set its soaking time. The setting time can be Figure 1 It is known that the morphology of the fly ash particles prepared is 72 hours, and finally 24 hours of hot air curing at 70°C is carried out. After completion, it is placed at room temperature for curing until the age of 7d. Figure 2 .
[0061] Depend on Figure 2 It can be seen that the fly ash geopolymer (b) prepared in the present application has more aggregated surface particles than the conventional high temperature curing product (a), which can prove that the reaction degree of the fly ash in the present application is more complete.
[0062] Depend on Figure 3 It can be seen that after experimental testing, the performance is shown in Table 3 below:
[0063] Table 3
[0064]
[0065] Compared with traditional high-temperature curing, the compressive strength after immersion is increased by more than 5%.
[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for improving the reaction degree of fly ash-based geopolymer, characterized in that: The steps include: (1) Determine the amount of fly ash, obtain the unknown amounts of NaOH, Na2SiO3 and water through formulation design, and perform a polymerization reaction of fly ash, NaOH, Na2SiO3 and water to obtain geopolymer A; (2) Soaking geopolymer A in alkali solution to carry out a secondary polymerization reaction to obtain geopolymer B; (3) Determine the time of secondary polymerization reaction by inductively coupled plasma mass spectrometry; (4) After heating and curing the geopolymer B, it can be cured at room temperature until the curing age; The method for designing the fit in step (1) includes: S1. Determine the liquid-solid ratio, exciter modulus, OH - molar concentration, the liquid-to-solid ratio is the ratio of the sum of water and solid, the activator modulus is the SiO2 / Na2O ratio after the composite activator is prepared by NaOH and Na2SiO3, the OH - Molar concentration refers to NaOH solutions of different molar concentrations; S2. Determine the amount of fly ash, and count the unknown quantities of Na2SiO3, NaOH and water as A, B and C. The specific calculation method is: in, is the concentration of sodium silicate solution; FA is the mass of fly ash; is the modulus of sodium silicate solution; Sodium silicate solution Content; Sodium silicate solution Content; Sodium hydroxide powder Content; The concentration of the alkali solution in step (2) is designed to be: The geopolymer A prepared in step (1) is soaked in a NaOH solution at room temperature and prepared according to the alkali solution concentration designed in the mix ratio; Geopolymer A is immersed in a volume of 1000cm 3 The concentration test was conducted in a solution with a solid-liquid ratio of 0.0626 to 0.25; the concentration of the NaOH solution of the sample that was relatively intact and not cracked after immersion was selected as the concentration of the alkali solution; The inductively coupled plasma mass spectrometry method described in step (3) includes: During the soaking process of step (2), sampling is performed at different time intervals, and the solution is collected after filtering and dilution; The obtained solution was detected by inductively coupled plasma mass spectrometry, and the dissolution curves of Si and Al elements were drawn. The time period of secondary precipitation was determined by finding the descending section of the dissolution of Si and Al elements in the fly ash polymer, thereby determining the end time of the secondary polymerization reaction.
2. The method for improving the reaction degree of fly ash-based geopolymer according to claim 1, characterized in that: The concentration of the NaOH solution is three samples of two identical concentrations and one different concentration; The soaking time is 7 to 10 days; When the polymer does not crack after being immersed in two NaOH solutions with different concentrations, the higher concentration is selected as the alkali solution concentration.
3. The method for improving the reaction degree of fly ash-based geopolymer according to claim 1, characterized in that: At least one of the following conditions is met: The time interval is 4 to 16 hours; The amount of the sampling solution is 1-3 ml; The filtering method is syringe filter filtration. When the syringe filter is used for filtration, the diameter of the syringe is 0.1-0.5 μm. The dilution multiple is 20 to 100 times.
4. The method for improving the reaction degree of fly ash-based geopolymer according to claim 1, characterized in that: The heating and curing method described in step (4) is to place the mixture in a hot air oven for heating and curing; When the hot air box is used, the temperature of the heating and curing is 60-80°C; When the hot air box is used, the heating and curing time is 24 to 48 hours.
5. The method for improving the reaction degree of fly ash-based geopolymer according to claim 1, characterized in that: The nursing period in step (4) is 5 to 10 days.
Citation Information
Patent Citations
Method for manufacturing NaA molecular sieve block by means of coal ash base geopolymer
CN105253897A
Method for preparing A-type fly ash-based molecular sieve by dynamic self-adjusting hydrothermal method
CN111533135A